Effect of pterostilbene on in vitro drug metabolizing enzyme activity - Ahmed A. Albassam; Reginald F. Frye (Elsevier, 2019)
Pterostilbene is a natural polyphenol compound found in small berries that is related to resveratrol, but has better bioavailability and a longer half-life. The purpose of this study was to assess the potential inhibitory effect of pterostilbene on in vitro drug metabolism. The effect of pterostilbene on cytochrome P450 (CYP) and UDP-glucuronosyltransferase (UGT) enzyme activities were studied using the enzyme-selective substrates amodiaquine (CYP2C8), midazolam (CYP3A4), estradiol (UGT1A1), serotonin (UGT1A6) and mycophenolic acid (UGT1A8/9/10). The IC50 value was used to express the strength of inhibition. Further, a volume per dose index (VDI) was used to estimate the potential for in vivo interactions. Pterostilbene significantly inhibited CYP2C8 and UGT1A6 activities. The IC50 (mean ± SE) values for CYP2C8 and UGT1A6 inhibition were 3.0 ± 0.4 µM and 15.1 ± 2.8 µM, respectively; the VDI exceeded the predefined threshold of 5 L/dose for both CYP2C8 and UGT1A6, suggesting a potential for interaction in vivo. Pterostilbene did not inhibit the metabolism of the other enzyme-selective substrates. The results of this study indicate that pterostilbene inhibits CYP2C8 and UTG1A6 activity in vitro and may inhibit metabolism by these enzymes in vivo. Clinical studies are warranted to evaluate the in vivo relevance of these interactions. Keywords: Pterostilbene, CYP2C8, UGT1A6, Amodiaquine, N-desethylamodiaquine, Pioglitazone, Hydroxypioglitazone, Serotonin, Serotonin glucuronide, Enzyme inhibition